Status and distribution of the globally threatened Bristled Grassbird Chaetornis striata (Jerdon, 1841) (Fam. Sylviidae) in Nepal - Baral, Hem Sagar; Wattel, Jan; Brewin, Philip A; Ormerod, Steve J (The Initiation, 2014)
Lowland grasslands in Nepal were thoroughly surveyed in 1996-1999 to assess the status and distribution of the globally threatened Bristled Grassbird Chaetornis striata. Birds were located on foot, from elephants and from jeeps by sight and sound backed up by mistnets and tape playback. The status information was updated again by visiting these areas in 2010-2012. Bristled Grassbirds were recorded in Sukla Phanta and Koshi Tappu Wildlife Reserves, and Chitwan National Park where most of the Nepal population is confined. From the research, it was found that they were most associated with newly formed Saccharum and Imperata dominated grasslands during summer. The low numbers present during winter suggested that this species was primarily a summer migrant to Nepal. A total population for Nepal is presented based on a reliable density estimate. Loss and degradation of grassland habitat and invasion of Mikania micrantha were identified as the major threats. Further research on migratory status, better control of cattle grazing inside reserves, expansion of Protected Areas to include more grassland, and listing of Bristled Grassbird as protected under the wildlife law of Nepal for its conservation are highly recommended. DOI: http://dx.doi.org/10.3126/init.v5i0.10244 The Initiation 2013 Vol.5; 1-15